The Routledge international handbook of homicide investigation - Allsop, Cheryl; Pike, Sophie (Routledge international handbooks, 2024)
"The Routledge International Handbook of Homicide Investigation will be the first of its kind to bring together research and personal insights from detectives, practitioners, academics and experts internationally on various complexities that are involved in the investigation of homicides. The handbook discusses the challenges faced by homicide detectives especially since not every investigation will demand the same approach. The tools, techniques and expertise required also vary according to the type of homicide that is investigated. This handbook brings these issues and opportunities to the forefront, while also illustrating the wider complexities and emotional impact of homicide investigations on detectives and those bereaved by homicide. Divided into four parts, part one provides chapters that explore homicide investigation across the globe. Part two and three offer an up-to-date insight into the ever-evolving tools and techniques that are used during a homicide investigation and explore how specific types of homicides are investigated. Part four considers both those directly affected by the homicide and the role of indirect victims in the investigation, including the impact of homicide and its investigation. Chapters also consider some recent developments in homicide investigation that may shape its future, as well as current issues that are facing homicide detectives. Providing cutting edge research on every step of the criminal homicide investigation process, this handbook is essential reading for scholars, students and practitioners interested in homicide investigation"--